From soil to air: exploring two novel approaches to studying cryptic aspects of insect ecology - Gulutzo, Sophia Maria, author; Mola, John M., advisor; Pearse, Ian, committee member; Pejchar, Liba, committee member (Colorado State University. Libraries, 2025)
Insects play critical roles in forest ecosystems; however, their overwintering ecology and spatial behavior remain poorly understood due to methodological challenges in observing their cryptic life stages and movements. This thesis integrates two complementary approaches to address these gaps in montane lodgepole pine forests of Colorado. First, we used soil emergence traps to investigate how fine-scale microhabitat conditions—including canopy cover, duff depth, basal area, and ground cover—affect spring insect abundance and emergence phenology. Across 77 traps, we recorded 1,286 insects, dominated by Coleoptera, Hymenoptera, and Hemiptera. While patterns of abundance and emergence timing were highly variable, no environmental predictors showed statistically significant effects, suggesting that unmeasured microclimatic factors and species-specific traits likely drive overwintering outcomes. Second, we evaluated the feasibility of applying very high frequency (VHF) radio telemetry to bumble bees (Bombus spp.), testing morphological predictors of flight success in mock-tag trials and conducting field deployments with Lotek NanoPin transmitters. Body mass emerged as the dominant determinant of flight ability, with a threshold of ~310 mg required for even-odds flight, a size exceeded primarily by queens and large workers. Field trials revealed limited relocation success, with signals often lost within minutes to hours, underscoring the influence of terrain, vegetation, and receiver strategy on detection. Together, these studies highlight both the promise and constraints of emerging methods for studying cryptic phases of insect ecology. Soil emergence traps provide community-level insight into overwintering dynamics, while telemetry—though currently constrained by body size and signal range—offers potential for directly locating nests and tracking movement. By pairing habitat-based and individual-based approaches, this work advances understanding of insect persistence and phenology in montane forests and establishes methodological baselines to inform future research under changing climatic conditions.
Keywords: bee overwintering; bumble bees; radio telemetry; Bombus; bee nesting; insect overwintering